Pelatihan Dan Pendampingan Meningkatan Kualitas SDM Dan Pendapatan UMKM Kota Bogor - Henry Sumurung Octavian; Yayuk Nurjanah; Heri Sastra; Jan Horas Veryady Purba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
What is really felt about micro businesses in the development of the Indonesian economy is the absorption of labor, increasing income and social welfare. Apart from these advantages, of course there are weaknesses that must be considered, several weaknesses of micro businesses are inhibiting factors for the development of MSME businesses, including the quality of human resources. Improving the quality of human resources through various means needs to be improved, such as training and education needed to increase the competitiveness of micro businesses towards larger and more advanced business scales in the future, with better management, using safe materials and contributing to creating a healthy business environment. Types of training such as management training, entrepreneurship, as well as processing their industrial waste better and more professionally, so that they are expected to be able to make quality and healthy products. The purpose of this assistance and training is to determine the effect of training on income. The training and mentoring method is by collecting data using questionnaires, interviews and presentations. The results of this mentoring are that mentoring and training really help significantly with income, training and mentoring have a positive contribution to increasing income. If the quality of human resources improves through training and mentoring activities, then business income will increase. Keywords: quality of human resources, training, and income.